Electrochemical Preparation and Transformation of Sulfonium Salts - Takuya Michiyuki; Lutz Ackermann (ChemElectroChem)
Abstract Sulfonium salts are typically bench‐stable and readily available reagents that showcase diverse chemical reactivities. Owing to these synthetically valuable features, sulfonium salt chemistry has witnessed considerable momentum over the past decades. Particularly, the merger of sulfonium reagents and electrosynthesis enabled the utilization of electric current in place of cost‐intensive and hazardous chemical redox agents to maximize the attractive characteristics of sulfonium salts. Additionally, electrochemistry has allowed chemists to dial in the desired redox potential, offering selective access to target products that are otherwise unattainable by either thermal or photochemical manifolds. These advantages of electrochemistry led to major advances in sulfonium salt chemistry. Thus, we, herein, provide an overview of early pioneering findings and recent progress devoted to organic electrosynthesis associated with sulfonium salts until December 2024, aiming to stimulate future progress in this rapidly evolving arena.